2011
DOI: 10.5964/ejop.v7i3.146
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy of ultra-orthodox Jews in Israel – A qualitative assessment of conflicts and reconciliations

Abstract: The ultra-orthodox Jewish community in Israel is highly homogeneous and is virtually isolated from the surrounding secular society. Nevertheless, in recent years some openness to psychotherapy has emerged. In this paper the first author, herself a member of the ultra-orthodox community and a psychotherapist, presents a series of analyses and discussions of the major issues raised by therapy amongst members of this community. This study had two main objectives: a) a qualitative assessment of possible conflicts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There is extensive literature on the associations between religion and mental treatment in traditional societies in general (Andersen, Oades, & Caputi, 2003; Weaver, Pargament, Flannelly, & Oppenheimer, 2006) and in Ultra-Orthodox society in particular (Hess & Pitariu, 2011; Pirutinsky, Rosmarin, Pargament, & Midlarsky, 2011). Although studies have suggested that spirituality can be a source of support in times of crisis by enhancing physical and psychological functioning (Andersen et al., 2003; Pargament & Saunders, 2007), other work has suggested that negative religious coping, manifested by activating anger towards God, decreased engagement in religious activities, as well as increased guilt and doubts can be an obstacle to mental health and lead to a decline in mental health (Exline & Rose, 2005; Pargament, Koenig, Tarakeshwar, & Hahn, 2004) (Ano & Vasconcelles, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is extensive literature on the associations between religion and mental treatment in traditional societies in general (Andersen, Oades, & Caputi, 2003; Weaver, Pargament, Flannelly, & Oppenheimer, 2006) and in Ultra-Orthodox society in particular (Hess & Pitariu, 2011; Pirutinsky, Rosmarin, Pargament, & Midlarsky, 2011). Although studies have suggested that spirituality can be a source of support in times of crisis by enhancing physical and psychological functioning (Andersen et al., 2003; Pargament & Saunders, 2007), other work has suggested that negative religious coping, manifested by activating anger towards God, decreased engagement in religious activities, as well as increased guilt and doubts can be an obstacle to mental health and lead to a decline in mental health (Exline & Rose, 2005; Pargament, Koenig, Tarakeshwar, & Hahn, 2004) (Ano & Vasconcelles, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…I stopped reading in the middle, the descriptions were horrifying, full of sexual thoughts […] I was disgusted. (Therapist 4)To resolve these doubts, the participants preferred consulting with their rabbis as the supreme authority, or reading religious sources for answers (Hess & Pitariu, 2011). In addition, many therapists stated that references to religious explanations moderated and lessened the tension between the two worlds of religion and therapy and served as a bridge in facilitating disclosure and reflection on familial relationships or intragenerational frameworks.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to psychotherapeutic treatments in the Ultra-Orthodox community, the research literature is quite fertile (Bruchin, 2014;Hess & Pitariu, 2011;Hoffman & Ben-Shalom, 2001;Huppert et al, 2007;Schnall, 2006), in contrast to music therapy in the Ultra-Orthodox community which has insufficiently explored. However, several important factors have been noted in distinguishing the uniqueness of music therapy with Ultra-Orthodox children, compared to music therapy with other populations (Seri, 2013):…”
Section: Music Therapy With Ultra-orthodox Childrenmentioning
confidence: 99%
“…Although there is now greater acceptance of psychotherapy and outside help, especially for children at risk [ 27 ], studies show that the intercultural gap still impacts the ultra-Orthodox encounter with psychotherapy and creates significant conflicts [ 28 ]. For example, ultra-Orthodox clients may experience a conflict between dealing with difficulties privately and autonomously within the community and seeking help from external sources [ 11 ], difficulty opening up about issues that are not culturally acceptable [ 29 ], expecting practical solutions that are limited to what is allowed and forbidden according to culture and religion [ 30 ], and fear of stigma that may lead to negative consequences for future matchmaking of the individual and other family members, the ability to get a job in the community, social ties, and integration in educational institutions [ 31 , 32 ]. In child therapy, these difficulties can be intensified for the ultra-Orthodox client’s parents, who feel a sense of responsibility for the child’s religious and spiritual education [ 33 ].…”
Section: Introductionmentioning
confidence: 99%